Energy and poverty in Bangladesh: sustainability accounting perspectives - Khan, M.; Hossain, A.; Marinova, Dora (World Business Institute, 2016)
Poverty in rural Bangladesh is commonly explained with lack of reliable energy supply. Intrinsically motivated, the purpose of this research is to put such a rhetoric to the test. Following a qualitative analysis of traditional wisdom data, including teachings of the mystic Baul-philosophers, the main finding is that energy and poverty are largely unrelated but linked to the social, geo-environmental and cultural norms of Bangladesh. A push to fossil fuel-based electrification to reduce poverty is unsustainable with renewable energy being the best option instead. The study concludes that rural resilience largely depends on practicing sustainability accounting for natural resources conservation.